Problems of approximation theory in linear spaces - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We present a survey of results related to the approximation characteristics of the spaces $S^{ρ}_{φ}$ and their generalizations. The proposed approach enables one to obtain solutions of problems of classical approximation theory in abstract linear spaces in explicit form. The results obtained yield statements that are new even in the case of approximations in the functional Hilbert spaces $L_2$.